Targeting Membrane Transporters and Receptors as a mean to Optimize Orally Delivered Biotechnological based Drugs through Nanoparticle Delivery Systems - Pereira, Carla; Araujo, Francisca; L. Granja, Pedro; A. Santos, Helder; Sarmento, Bruno (Current Pharmaceutical Biotechnology, 2014)
Biotechnology has been used for a long period of time in the most diverse scientific areas, making its journey in close contact with pharmaceutical sciences. Among the several products manufactured in biotechnological industry, peptides and proteins are in the front-line for the treatment of several diseases due to their selectivity, effective action and few side effects. However, orally administration route is not feasible for peptide and protein drugs due to the several physical and chemical barriers along the gastrointestinal tract and, consequently, are delivery by parental routes. Between several strategies, it is believed that delivery systems can render the oral route viable, increasing the convenience and compliance of patients and enhancing drugs therapeutic effect. Recently, more specific strategies have been explored to better direct the delivery systems, achieved by their functionalization with ligands that specifically bind to membrane transporters and receptors existing along the gastrointestinal way. Despite the promising results obtained with functionalized nanoparticles, the oral delivery of peptides/proteins is still limited and a lot of research is required to successfully introduce nanoparticles in the clinical field.
Keywords: oral delivery